2021
DOI: 10.3389/fnins.2021.755709
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intermittent Theta Burst Stimulation on Functional Brain Network Following Stroke: An Electroencephalography Study

Abstract: Objective: Intermittent theta burst stimulation (iTBS) is a special form of repetitive transcranial magnetic stimulation (rTMS), which effectively increases cortical excitability and has been widely used as a neural modulation approach in stroke rehabilitation. As effects of iTBS are typically investigated by motor evoked potentials, how iTBS influences functional brain network following stroke remains unclear. Resting-state electroencephalography (EEG) has been suggested to be a sensitive measure for evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 51 publications
0
30
2
Order By: Relevance
“…RMT was determined as the minimum intensity required to evoke 5 out of 10 MEPs greater than 50 μV at rest ( Chen et al, 1998 ). A neuronavigation system (Visor2, ANT Neuro, Hengelo, Netherlands) was used to ensure consistent coil positioning over the optimal scalp position (i.e., motor hotspot) throughout the experiment ( Ding et al, 2021a , c ). For the individuals in whom MEPs in the IH cannot be elicited even with 100% MSO ( n = 6 in the Active iTBS group and n = 5 in the Sham iTBS group), RMT in the IH was considered as 100% maximum stimulator output (MSO).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…RMT was determined as the minimum intensity required to evoke 5 out of 10 MEPs greater than 50 μV at rest ( Chen et al, 1998 ). A neuronavigation system (Visor2, ANT Neuro, Hengelo, Netherlands) was used to ensure consistent coil positioning over the optimal scalp position (i.e., motor hotspot) throughout the experiment ( Ding et al, 2021a , c ). For the individuals in whom MEPs in the IH cannot be elicited even with 100% MSO ( n = 6 in the Active iTBS group and n = 5 in the Sham iTBS group), RMT in the IH was considered as 100% maximum stimulator output (MSO).…”
Section: Methodsmentioning
confidence: 99%
“…iTBS was applied over the motor hotspot in the ipsilesional M1. The iTBS stimulation intensity was set at 70% RMT in the IH ( Volz et al, 2016 ; Ding et al, 2021c ). During the application of iTBS, participants were instructed to remain static.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, connectivity can also be modulated with neurostimulation techniques usually targeted at regulation of excitability (Grefkes and Fink, 2012). TBS has been shown to modulate both excitability (Ackerley et al, 2010;Boddington et al, 2020) and connectivity (Ding et al, 2021) in stroke patients and healthy controls (Nettekoven et al, 2014), although results in the latter showed that, even though both processes happen simultaneously, a correlation between them could not be found.…”
Section: Tying Excitatory-inhibitory Homeostasis and Functional Reorganization In Stroke Recoverymentioning
confidence: 99%
“…Not only that, but TBS is thought to potentiate cortical excitability ( Huang et al, 2005 ) and, when applied to stroke rehabilitation, can be used to stimulate increases in excitability of the ipsilesional cortex that relate to clinical recovery ( Di Lazzaro et al, 2008 ; Ackerley et al, 2010 ; Boddington et al, 2020 ), although the specific contribution of each particular area (e.g., somatosensory and motor cortices) to motor recovery is not yet fully understood ( Meehan et al, 2011 ). Interestingly, recent results suggest that TBS further acts on functional connectivity, contributing to the recovery of important properties such as interhemispheric connectivity and global efficiency ( Ding et al, 2021 ). Taking that into consideration, it is reasonable to believe that mesoscale excitability and large-scale connectivity are synergetic processes and can be simultaneously modulated by the same techniques, fitting the hypothesis that EI homeostasis is an underlying driver of cortical reorganization.…”
Section: Diaschisis and Excitabilitymentioning
confidence: 99%